La politique commerciale fédérale et l’économie québécoise - Tremblay, Rodrigue (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractIt is argued in this paper that both normative and objective considerations must be taken into consideration in the formulation of tariff policy. Moreover, it is shown that static and partial equilibrium analyses can be disastrously misleading in guiding the framing of tariff policy.Regarding the regional impact of tariffs, it is shown that within a monetary union, interregional trade flows reflect absolute production and transport cost advantages and that the non-realization of perfect domestic mobility of factors of production entails social and private adjustment costs that must be reckoned with in the cost-benefit analysis of any shift in trade policy.From the standpoint of Quebec, a French-speaking political entity, the Canadian trade area is far from being optimal. The tendency for Canadian market-oriented economic activity to polarize in Ontario behind tariff walls, accompanied by a large movement of foreign enterprises, pushes the Quebec economy towards the least attractive and the most vulnerable industries among those oriented towards the Canadian common market. A rationalization of these laggard Quebec industries and an up-grading of resources-oriented economic activity would then benefit from the removal of both Canadian and American tariffs. Among Canadian trade options, therefore, Quebec would potentially benefit most from a gradual move toward a North-American free trade area, with ad hoc measures for certain industries, but should reject the world-wide free trade and unilateral free trade options because of the serious industrial dislocations and factors of production outflows they would create.